Cistus creticus subsp. eriocephalus as a Model for Studying Plant Physiological and Metabolic Responses to Environmental Stress Factors. Issue 12 (December 2015) - Paolessi, Paola; Nicoletti, Marcello; Catoni, Rosangela; Puglielli, Giacomo; Toniolo, Chiara; Gratani, Loretta
Abstract: Variations in physiology and metabolic products of Cistus creticus subsp. eriocephalus along an altitudinal gradient (350–750 m.a.s.l.) within the Monti Lucretili Regional Natural Park (central Italy) were studied. The results showed that the phenol production was in relationship with the net photosynthetic rates and the chlorophyll content. In particular, the increasing caffeic acid (CA) content with altitude suggested its role in providing an additional photo‐protection mechanism, by its ability to consume photochemical reducing power and acting as an alternative C‐atom sink under high light conditions. The metabolic production was tested by high performance thin layer chromatography (HPTLC) fingerprint analysis, highlighting the potential of this technique in biologic studies. Abstract :